2012
DOI: 10.4137/ccrep.s9189
|View full text |Cite
|
Sign up to set email alerts
|

Ureteritis Cystica: Important Consideration in the Differential Diagnosis of Acute Renal Colic

Abstract: Ureteritis cystica is an uncommon cause of acute renal pain. The aetiology remains unclear and the diagnosis may be difficult to establish. We report the case of a 29 year old woman with a history of repeated urinary tract infections presenting with acute renal colic in the absence of lithiasis. We review the diagnostic tools available to make the diagnosis and the recent pertinent literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…UC occurs predominantly in women, and is usually localized in the upper renal tract (1,4). The presentation of cystic urethritis associated to a ureteral polyp is very uncommon and usually more than a few ureteral cysts are present (4,6). In this particular case, the patient had a very rare association between cystic ureteritis to a ureteral benign tumor.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…UC occurs predominantly in women, and is usually localized in the upper renal tract (1,4). The presentation of cystic urethritis associated to a ureteral polyp is very uncommon and usually more than a few ureteral cysts are present (4,6). In this particular case, the patient had a very rare association between cystic ureteritis to a ureteral benign tumor.…”
Section: Discussionmentioning
confidence: 80%
“…Currently, CT scan is the preferred imaging choice, which allows differentiation of epithelial polyps from other ureteral filling defects. Definitive diagnosis usually requires cystoscopy, ureteroscopy and biopsy or complete resection of the lesions (3,4,6,10).…”
Section: Discussionmentioning
confidence: 99%
“…It is a proliferative condition characterized by multiple cysts and filling defects in the urothelium. It has classically been documented in older female patients with a history of recurrent urinary tract infections or kidney stones and can be challenging to diagnose [ 2 ]. Most of the literature points toward unilateral ureteral involvement, with rare cases of bilateral findings, as described in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the causes of UC to be nephrolithiasis and urinary tract infections. Other etiological factors that have been postulated include schistosomiasis, vitamin A excess, and increased immunoglobulin A [ 2 ]. In one study, UC was found in a patient following formalin treatment for cyclophosphamide-induced hemorrhagic cystitis [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation